Reduction-controlled substrate release from a polymer nanosphere based on a viologen-cavitand. Issue 74 (22nd July 2016) - Sultanova, Elza D.; Atlanderova, Anna A.; Mukhitova, Rezeda D.; Salnikov, Vadim V.; Osin, Yuriy N.; Ziganshina, Albina Y.; Konovalov, Alexander I.
Abstract : In this article, we present a new polymeric nanosphere (p(MVCA- co -SS)) for redox-controlled substrate release. Abstract : In this article, we present a new polymeric nanosphere (p(MVCA- co -SS)) for redox-controlled substrate release. The nanosphere consists of a hydrophobic core with disulfide bridges stabilized by the viologen-resorcinarene cavitand shell. The nanosphere is sensitive to thiol-containing reducing agents: glutathione (GSH) and dithiothreitol (DTT). GSH destructs the hydrophobic core of p(MVCA- co -SS) while DTT integrates into the core increasing its size. The nanosphere as shown can be used as nanocarriers for the redox-controlled substrate release for the fluorescent dyes (pyrene, rhodamine b and fluorescein).